Analysis of NPK Phonska Fertilizer Bag Defects Using FTA and FMEA Methods at PT XYZ - Prashodang, Tryandika Rizkat; Aryanny, Enny (Newinera Publisher, 2025)
This study aims to analyze the defects in NPK Phonska fertilizer bags at PT XYZ, focusing on three main types of defects: torn bags, loose seams, and uneven stitching. From February 2024 to January 2025, a total of 33,159 tons of NPK Phonska bags were found defective, representing 6.639% of the total production. The probability of the defects occurring were calculated as follows: torn bags with a probability of 2.219%, loose seams with 2,003%, and uneven stitching with 1.388%. The research was conducted using Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA) methods to identify the root causes and prioritize improvements. FTA was used to trace the causes of defects from a top-down perspective, while FMEA helped assess potential failures and their impacts, assigning Risk Priority Numbers (RPN) to prioritize corrective actions. The findings revealed that human errors, machine malfunctions, and inadequate work environments are the primary causes of the defects. The study concluded that improving the bagging process requires adding operators, implementing a rolling work system, conducting regular machine calibration, increasing workforce capacity to meet production deadlines, and ensuring a safe working environment. The recommendations aim to reduce defect rates and enhance productivity in the warehouse.